Legal Review of the Performance of Firefighters and Rescue Workers in Deli Serdang - Sunardi Petrus Sembiring; Heriansyah Heriansyah; Dewi Robiyanti (LEGAL BRIEF, 2023)
Fire and Rescue or abbreviated as Fire and Rescue are implementing elements of the Government which have the responsibility to assist the community in handling fires and rescue. The research objective was to find out the legal review regarding the performance of firefighters and rescue workers in Deli Serdang Regency. And it is necessary to have a legal study on how to deal with fires in accordance with rescue procedures from the government which can create common perceptions and uniformity of ways of acting for all personnel involved. The type of research in this paper is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive, namely explaining the problem according to the research title. The data used as primary legal materials include Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 16 of 2020 Concerning Nomenclature Guidelines for Provincial and District/City Fire and Rescue Services, and secondary legal materials in the form of books, journals, writings, media , and documents or other information related to the research title. By carrying out the procedures from the government, efficient suppression efforts can be achieved in deploying personnel to minimize losses and work as optimally as possible in blackout operations and rescue operations. Therefore, it is recommended for Firefighters and Rescue Executors to improve performance and timeliness, quality of facilities and infrastructurein tackling fire disasters and better rescue so that more and more people are saved. Especially to improve the procedures, rules and performance of officers to do more optimal fire prevention and rescue so that they run according to community expectations and regulation from government.